Potential of PEGylated Toll-Like Receptor 7 Ligands for Controlling Inflammation and Functional Changes in Mouse Models of Asthma and Silicosis - Ferreira, Tatiana Paula Teixeira; Mariano, Lívia Lacerda; Ghilosso-Bortolini, Roberta; Arantes, Ana Carolina Santos de; Fernandes, Andrey Junior; Berni, Michelle; Cecchinato, Valentina; Uguccioni, Mariagrazia; Maj, Roberto; Barberis, Alcide; Silva, Patricia Machado Rodrigues e; Martins, Marco Aurélio (Frontiers in Immunology, 2016)
Prior investigations show that signaling activation through pattern recognition receptors can directly impact a number of inflammatory lung diseases. While toll-like receptor (TLR) 7 agonists have raised interest for their ability to inhibit allergen-induced pathological changes in experimental asthma conditions, the putative benefit of this treatment is limited by adverse effects. Our aim was to evaluate the therapeutic potential of two PEGylated purine-like compounds, TMX 302 and TMX 306, characterized by TLR7 partial agonistic activity, therefore expected to induce lower local and systemic adverse reactions. In vitro approaches and translation to murine models of obstructive and restrictive lung diseases were explored. In vitro studies with human PBMCs showed that both TMX-302 and TMX-306 marginally affects cytokine production as compared to equivalent concentrations of the TLR7 full agonist, TMX-202. The PEGylated compounds did not induce monocyte-derived DC maturation or B cell proliferation, differently from what observed after stimulation with TMX-202. Impact of PEGylated ligands on lung function and inflammatory changes was studied in animal models of acute lung injury, asthma and silicosis following LPS, allergen (ovalbumin) and silica inhalation, respectively. Subcutaneous injection of TMX-302 prevented LPS- and allergen-induced airway hyper-reactivity (AHR), leukocyte infiltration and production of pro-inflammatory cytokines in the lung. However, intranasal instillation of TMX-302 led to neutrophil infiltration and failed to prevent allergen-induced AHR, despite inhibiting leukocyte counts in the BAL. Aerolized TMX-306 given prophylactically, but not therapeutically, inhibited pivotal asthma features. Interventional treatment with intranasal instillation of TMX-306 significantly reduced the pulmonary fibro-granulomatous response, the number of silica particles in lung interstitial space and improved respiratory function in silicotic mice. These findings highlight the potential of TMX-306, emphasizing its value in drug development for lung diseases, and particularly silicosis.